Pemaknaan Literasi Digital Sebagai Kesadaran Kritis Mahasiswa Ilmu Komunikasi Dalam Menghadapi Disinformasi di Media Sosial (Studi Fenomenologi pada Mahasiswa Ilmu Komunikasi UIN Sultan Syarif Kasim Riau) - Atjih Sukaesih; Yantos Yantos; Kodarni Kodarni (Yayasan Almanar Pujud, 2026)
The development of digital communication has changed the way students obtain, understand, and distribute information through social media. Students no longer merely act as message recipients but also actively produce and disseminate information in the digital space. This situation raises issues when the intensity of social media use is not balanced with critical digital literacy skills, especially in dealing with disinformation that develops through media algorithms and emotional narratives. This study aims to analyze the meaning of digital literacy as a form of critical awareness of Communication Science students in dealing with disinformation on social media. The study used a qualitative approach with a phenomenological method. The research informants were students of the Communication Science Study Program, Faculty of Da'wah and Communication, UIN Sultan Syarif Kasim Riau who actively use social media in academic and daily activities. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis was carried out interpretively through data reduction, theme categorization, and phenomenological meaning drawing. The results show that students interpret digital literacy not only as the technical ability to use media, but also the ability to verify information, understand algorithmic bias, and consider ethical aspects in digital communication. However, students' digital literacy practices are still influenced by emotional factors, identity affiliations, and the instant culture of social media. This research confirms that critical digital awareness is formed through students' academic experiences, social experiences, and ethical reflection in digital spaces. The research findings expand the study of digital literacy by positioning it as a reflective and ethical practice within the context of Islamic-based higher education.